Determination of intensity ratios of Nd, Cs, Zr and Sr against U and burn-up in simulated nuclear fuels by LA-ICPMS. Issue 4 (22nd March 2022) - Maity, U. K.; Manoravi, P.; Joseph, M.; Chandra, Manish; Natarajan, G.; Sivaraman, N.
Abstract : Applicability of LA-ICPMS for spatial profiling of non-isobaric isotopes in solid samples. Abstract : Laser ablation coupled with inductively coupled plasma mass spectrometry (LA-ICPMS) is employed in spatial profiling mode to determine the isotopic ratios and burn-up of simulated fast breeder reactor (FBR) fuel containing heavy element atoms (U) and various fission products (FPs), such as a burn-up monitor (Nd) and long lived (Zr and Sr), diffusible (Zr) and volatile (Cs) FPs, corresponding to different burn-ups varying from 0.7 to 15.4 atom percent (at%). Different laser spots on the fuel pellets are sampled across diametric directions to study spatial profiling. The present study demonstrates the application of LA-ICPMS for burn-up determination and potential spatial profiling by measuring the isotopic ratios of the selected elements of interest. Results of calibration plot, correlation coefficient (0.9998–0.99998), RSD (relative standard deviation, 0.1–0.9%) and accuracy (deviation < 1%) for potential spatial profiling are reported here. Outcomes from LA-ICPMS are validated by comparing with results obtained from liquid sampling ICPMS. The data obtained indicates the applicability of this technique for surface profiling. The reason for this achievement is discussed based on crater morphology and ablation characteristics. Furthermore, the use of an in-house designed multi-sample laser ablation cell is described, which enables continuous measurements without interrupting the ICP, indicating its advantages over a single sample LA cell.